Pengaruh Diversifikasi Produk, Struktur Modal, Perputaran Modal Kerja, dan Ukuran Perusahaan terhadap Profitabilitas Perusahaan - Neks Triani; Zahra Wahyuni; Arnadi Chairunnas (Prodi Akuntansi FE Universitas Maritim Raja Ali Haji, 2022)
This study aims to examine the effect of Product Diversification, Capital Structure, Working Capital Turnover, and Company Size on Profitability of Telecommunication Sub-Sector Companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2020 period partially and simultaneously. The data used is secondary data which is accessed through the website www.idx.co.id. The sampling technique in this study is a saturated sample/census, where all the population is used as a sample consisting of 5 telecommunications sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2020 period. The data analysis used is panel data regression with the help of the Eviews 9 tool. The results show that, partially, product diversification and working capital turnover have no significant effect on profitability. While the capital structure and size of the company have a significant effect on profitability. While simultaneously all independent variables affect the dependent variable, with a coefficient of determination of 65.27%.